The prohibition of financing of terrorism in the light of international law and regulations of the Republic of Serbia - Cmiljanić Bajo M. (Temida)
Terrorist acts are sometimes carried out in order to obtain funds for financing terrorist organizations and terrorist actions. Therefore, due attention in considering the forms of combat against terrorism has been paid to the connection between money and violence. The issue of prohibition of financing of terrorism is the subject of many international legal documents. Republic of Serbia has devoted many normative documents to this problem, that are harmonized with the international obligations accepted upon the signing of international treaties. The task of this paper is to show the basic norms of international law and the laws of the Republic of Serbia regarding the prohibition of financing of terrorism.